2017
DOI: 10.1038/s41598-017-11869-8
|View full text |Cite
|
Sign up to set email alerts
|

Power frequency magnetic field promotes a more malignant phenotype in neuroblastoma cells via redox-related mechanisms

Abstract: In accordance with the classification of the International Agency for Research on Cancer, extremely low frequency magnetic fields (ELF-MF) are suspected to promote malignant progression by providing survival advantage to cancer cells through the activation of critical cytoprotective pathways. Among these, the major antioxidative and detoxification defence systems might be targeted by ELF-MF by conferring cells significant resistance against clinically-relevant cytotoxic agents. We investigated whether the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 78 publications
(86 reference statements)
4
29
0
Order By: Relevance
“…Even though the possible association of ELF‐MF exposure with neurodegenerative diseases is still a matter of debate, experimental studies identifying the potential etiopathogenetic mechanisms elicited by ELF are still few. In this context, a key role of ELF in prompting neuronal damage has been assigned to redox imbalance, extensively documented in neuronal experimental systems, including SH‐SY5Y cells [Di Loreto et al, ; Luukkonen et al, ; Consales et al, ; Mattsson and Simkó, Falone et al, ]. We previously demonstrated that 50‐Hz MF (1 mT) triggers oxidative stress, protein carbonylation, and neuronal cell death, and sensitizes SH‐SY5Y cells to the PD MPP + neurotoxin in vitro [Benassi et al, ], thus highlighting a possible detrimental effect elicited by ELF in predisposing neurons to degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…Even though the possible association of ELF‐MF exposure with neurodegenerative diseases is still a matter of debate, experimental studies identifying the potential etiopathogenetic mechanisms elicited by ELF are still few. In this context, a key role of ELF in prompting neuronal damage has been assigned to redox imbalance, extensively documented in neuronal experimental systems, including SH‐SY5Y cells [Di Loreto et al, ; Luukkonen et al, ; Consales et al, ; Mattsson and Simkó, Falone et al, ]. We previously demonstrated that 50‐Hz MF (1 mT) triggers oxidative stress, protein carbonylation, and neuronal cell death, and sensitizes SH‐SY5Y cells to the PD MPP + neurotoxin in vitro [Benassi et al, ], thus highlighting a possible detrimental effect elicited by ELF in predisposing neurons to degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…In most occasions, the goals were to study the epidemiology of low intensity ELF MF [Kesari et al, ; Höytö et al, ]. Continuous exposure, low intensity ELF MF seems to induce hyperproliferation of neuroblastoma cells [Trillo et al, ; Falone et al, ], supporting the IARC definition of EMF/MF as potential carcinogens. A 75 Hz, 2 mT MF lowered the proliferation rate of neuroblastoma SH‐SY5Y cells [Osera et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study ELF-EMF promoted a more malignant phenotype in neuroblastoma cells [ 27 ]. ELF-EMF induced a proliferative and survival advantage by activating key redox-responsive antioxidative and detoxification cytoprotective pathways associated with a more aggressive behaviour of neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%